Effectiveness of Workshop on Evaluation Methodology for Medical Teachers - Chinmay Shah; P. A. Gokhale; H.B. Mehta (Indian Association of Preventive and Social Medicine, 2011)
A workshop on evaluation methodology was designed at Government Medical College, Bhavnagar. The workshop comprised of six modules namely: Mechanics of Paper setting, MCQ formulation & Item analysis, Mini CEX, OSPE, OSCE and Structured Viva. Study was carried out with aim to find out effectiveness of workshop in changing knowledge and attitude towards different evaluation methodology. Method: Instruction was provided during a one day workshop with eight hours interactive sessions. Medical teachers from different parts of Gujarat participated, and the instructors were experienced clinicians and educationist. Lectures, group discussions, case simulations, video presentations and role-plays were the forms of instruction. Results: Using standardized questionnaires, the participants rated the quality of the workshop highly. They considered it to be a feasible and appropriate educational intervention and that it had a positive impact on their teaching skills. Conclusion: This workshop showed that significant change in knowledge and attitude towards different aspects of medical Student Evaluation process . The results show that it is a suitable and effective educational intervention